2006
DOI: 10.1017/s1368980006009700
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of ‘extra’ foods (energy-dense, nutrient-poor) among children aged 16–24 months from western Sydney, Australia

Abstract: Objective: This study evaluates the contribution of energy-dense, nutrient-poor 'extra' foods to the diets of 16-24-month-old children from western Sydney, Australia. Design: An analysis of cross-sectional data collected on participants in the Childhood Asthma Prevention Study (CAPS), a randomised trial investigating the primary prevention of asthma from birth to 5 years. We collected 3-day weighed food records, calculated nutrient intakes, classified recorded foods into major food groups, and further classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 16 publications
7
42
0
Order By: Relevance
“…These results appear to justify numerous short-term studies that focus on strategies to get children to taste F/V and recommendations to increase variety and quantity consumed. [38][39][40][41] Numerous studies have documented frequent exposure to noncore foods 7,9,[42][43][44] and correspondingly high intakes 9,42 even in very young children. Evidence from a range of studies indicates that children's acceptance of novel foods is influenced by genetic taste preferences 18 as well as environmental factors, particularly repeated exposure (familiarity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results appear to justify numerous short-term studies that focus on strategies to get children to taste F/V and recommendations to increase variety and quantity consumed. [38][39][40][41] Numerous studies have documented frequent exposure to noncore foods 7,9,[42][43][44] and correspondingly high intakes 9,42 even in very young children. Evidence from a range of studies indicates that children's acceptance of novel foods is influenced by genetic taste preferences 18 as well as environmental factors, particularly repeated exposure (familiarity).…”
Section: Discussionmentioning
confidence: 99%
“…5 Various studies in children aged 0 to 3 years show that while up to one-third did not eat fruit or vegetables, 80% to 90% consumed noncore foods on the survey day, with the latter contributing up to 30% of energy intake. [6][7][8][9] This evidence indicates there are substantial dietary quality issues even in young children.…”
mentioning
confidence: 98%
“…38 Although these results are not easily comparable to other studies due to differences in methodology, 'extra' foods (energy-dense, nutrientpoor) have previously been shown to contribute substantially to the diet in other studies involving children o2 years. 13,15,17 Frequent exposure to specific foods during infancy has been shown to influence taste development and later food preferences. 2 This early learning is influenced by genetic susceptibilities, which include the innate preference for both sweet and salty tastes, and the rejection of sour and bitter flavours.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] In Australia, only four cross-sectional studies performed 47-10 years ago have reported dietary intakes in children aged 9 months, 15 16-24 months, 16 12-36 months 17 and 1-5 years; 18 moreover, there are no national dietary surveys of children o2 years. Nonetheless, these few studies have raised concerns about some characteristics of weaning diets, such as the excessive energy intake in infancy and toddlerhood 19 and also their overall quality.…”
Section: Introductionmentioning
confidence: 99%
“…Short questions about selected breastfeeding practices, food habits and physical activity levels will be used, which have been widely employed in population health surveys including the NSW Child Health Survey 2001 [38] and the Childhood asthma Prevention Study [39], and are supported by validity testing [40-42]. …”
Section: Design and Methodsmentioning
confidence: 99%